Porcine circovirus 3: a new challenge to explore - Silva, Rosecleer Rodrigues da; Silva, Diego Ferreira da; Silva, Victor Hugo da; Castro, Alessandra M. M. G. de (Frontiers in Veterinary Science, 2024)
The intensification of production processes, resulting from the rise in pork production, contributes to environmental changes and increased interaction between humans, animals, and wildlife. This favorable scenario promotes the spread of potent viral species, such as PCV3, increasing the potential for the emergence of new pathogenic agents and variants. These changes in the epidemiology and manifestation of swine diseases highlight the need for enhanced understanding and control.The current literature presents challenges in the classification of PCV3, with different groups proposing diverse criteria. Establishing common terminology is crucial to facilitate comparisons between studies. While consensus among experts is valuable, new approaches must be transparent and comparable to existing literature, ensuring reproducible results and proper interpretation, positively impacting public health.This study aims to review the literature on PCV3 infection, exploring its key aspects and highlighting unanswered questions. Understanding PCV3 is essential to address challenges in the Brazilian swine industry, ensuring the health and well-being of animals. Further research in this direction is necessary to improve the understanding and control of viral diseases, promoting global health.